Decision Support System for Selection of An Excellent-Students at Faculty Level in University of X Based on GAP Methods - Laga, Sinarring Azi; Sihotang, Ellen Theresia; Hermansyah, Deny; Hariyanti, Tika Ayu (LPPM Telkom University Surabaya, 2024)
The aim of this study is to develop a Decision Support System (DSS) for the selection of an excellent-students in one of the faculties of X University using the gap analysis method (GAP). It was used to identify differences between students' expectations of selection criteria and students' actual performance. A survey was conducted on 31 students to obtain the necessary data. The result of this study revealed a gap between students' expectations and performance regarding academic grades and participation in student organizations. The result before implementation GAP with profile matching there were 29 accurate with two inaccurate data (93.54%). After implemented, there were 30 accurate and one was inaccurate at 96.78%. The DSS used GAP is a relevant solution to reduce errors and more objective.